Overcoming debt, achieving financial freedom : 8 pillars to build wealth - Zuniga-Sanchez, Cindy (Ascent Audio, 2022)
In Overcoming Debt, Achieving Financial Freedom, lawyer, business owner, and first-generation professional Cindy Zuniga-Sanchez delivers a practical and actionable blueprint for financial independence. Full of easy-to-apply advice for young adults, students, and early-career professionals, the book is a holistic guide to responsibly managing money and debt while building your nest egg. In the book, you'll explore how to be a responsible consumer, how to budget, save, invest, pay off debt, build credit, and increase your income. You'll also understand much of what school didn't teach you about student loans. The author explains: strategies to create a realistic and actionable debt repayment plan that will save you money and time; strategies for maximizing your income by negotiating your salary and finding profitable "side hustles"; techniques for straightforward forms of investing that responsibly balance risk and reward; and the money strategies that she put into place and resources that she used to go from having six-figures of debt to a multiple six-figure net worth. An essential money resource for students, professionals, entrepreneurs, and anyone else hoping to reduce their financial stress and improve their lives, Overcoming Debt, Achieving Financial Freedom is the simple and powerful money guide you've been waiting for